Historia de la transfusión sanguínea - Sbarra, Noel Humberto (1940)
The author deals with "The discovery of blood circulation" in the first chapter exposing primarily the idea which the ancient had regarding this, arid then he mentions in continuation, the anatomical progress which prepared the ground for the new doctrine. Next he speaks of the precursors of the discovery of the blood circulation until the time of William Harvey; ending with the discovery of the capillaries, chyliferous vessels and lymphatics. In the second chapter he deals with "The history of blood transfusion" from the primitive time until the present, stopping in the procedure of the transfusion of citrated blood, without the addition of other substances, which is credited to the Argentine Professor Luis Agote. He makes a summary regarding the technique and methods of transfusion, blood groups, organization, etc., and finally mentions the two blood transfusion Congresses held at Rome (1935) and Paris (1937).